Impact of international shipping emissions on ozone and PM2.5 in East Asia during summer: the important role of HONO and ClNO2 - J. Dai; T. Wang (Atmospheric Chemistry and Physics, 2021)
Ocean-going ships emit large amounts of air pollutants such as nitrogen oxide (NOx) and particulate matter. NOx emitted from ships can be converted to nitrous acid (HONO) and nitryl chloride (ClNO2), which produce hydroxyl (OH) and chlorine (Cl) radicals and recycle NOx, thereby affecting the oxidative capacity and production of secondary pollutants. However, these effects have not been quantified in previous investigations of the impacts of ship emissions. In this study, a regional transport model (WRF-Chem) revised to incorporate the latest HONO and ClNO2 processes was used to investigate their effects on the concentrations of ROx (RO2 + HO2 + OH) radicals, ozone (O3), and fine particulate matter (PM2.5) in Asia during summer. The results show that the ship-derived HONO and ClNO2 increased the concentration of ROx radicals by approximately 2–3 times in the marine boundary layer. The enhanced radicals then increased the O3 and PM2.5 concentrations in marine areas, with the ship contributions increasing from 9 % to 21 % and from 7 % to 10 % respectively. The largest ROx enhancement was simulated over the remote ocean with the ship contribution increasing from 29 % to 50 %, which led to increases in ship-contributed O3 and PM2.5 from 21 % to 38 % and from 13 % to 19 % respectively. In coastal cities, the enhanced levels of radicals also increased the maximum O3 and averaged PM2.5 concentrations from 5 % to 11 % and from 4 %–8 % to 4 %–12 % respectively. These findings indicate that modelling studies that do not consider HONO and ClNO2 can significantly underestimate the impact of ship emissions on radicals and secondary pollutants. Therefore, it is important that these nitrogen compounds be included in future models of the impact of ship emissions on air quality.